Synthesis and evaluation of CuO and Co-doped CuO nanofibers as electrocatalysts for nitrate reduction to ammonia - Ehlde,Freja (2025)
This master thesis investigates the synthesis, structural characterization and electrochemical performance of copper(II) oxide (CuO) and cobalt-doped CuO nanofibers as electrocatalysts for the electrochemical nitrate reduction reaction (NO3-RR). The overarching aim is to assess their potential for sustainable ammonia production under ambient conditions. A series of exploratory synthesis trials revealed significant sensitivity to lab-specific conditions as well as process details. Based on these findings, a final synthesis protocol involving electrospinning and thermal treatment was established, yielding nanofibrous CuO structures with and without cobalt doping. The materials were characterized using scanning electron microscopy (SEM) and X-ray diffraction (XRD), confirming morphology, phase composition and cobalt integration. Electrochemical experiments were performed in a two-compartment H-cell at neutral pH, employing both untreated and pre-reduced electrodes. Faradaic efficiency (FE) and electrochemically active surface area (ECSA) were used as primary performance metrics. The results indicate that pre-reduction has a pronounced effect on ECSA and initial electrode behavior, suggesting surface restructuring or phase transitions. However, its impact on faradaic efficiency varied depending on applied testing potential, showing positive effects only at the first (lowest) overpotential tested. Co-doped electrodes demonstrated improved faradaic efficiency in the lower overpotential range, possibly due to increased defect density and modified electronic structure. Overall, this work emphasizes the dynamic nature of CuO-based catalysts during operation and the importance of pre-treatment history in performance evaluation. It also highlights the need for in situ or operando techniques to better capture transient surface states and guide catalyst optimization for selective NO3-RR to ammonia.
Keywords: ammonia synthesis; nitrate reduction; CuO; Co; doping; electrocatalysis; nanofibers; catalyst